Respuesta :
5.136 [tex]\times 10^{-9}[/tex] is the magnitude of the resultant force (caused by the other two masses) on the mass at the origin
Explanation:
Use Newton's law of gravitation [tex]F = \frac{G \times m1 \times m2}{r^{2} }[/tex]
G - gravitational force
m -mass of the object
[tex]F_{1}[/tex] (vertical force):
[tex]F_{1} = \frac{6.6726 \times 10^{-11} \times 3 \times 3 }{0.52^{2} }[/tex]
[tex]F1 = 2.220 \times 10^{-9}N[/tex]
[tex]F_{2}[/tex] (horizontal force):
[tex]F_{2} = \frac{6.6726 \times 10^{-11 \times 3 \times 3} }{0.36^{2} }[/tex]
[tex]F_{2} = 4.633 \times 10^{-9}N[/tex]
hence F on the mass of origin [tex]= \sqrt{(2.220 \times 10^{-9} )^{2} } + (4.633 \times 10^{-9} )^{2}[/tex]
[tex]F = 5.136 \times 10^{-9} N[/tex]
The magnitude of the resultant force (caused by the other two masses) on the mass at the origin should be [tex]5.136*10^9.[/tex]
Newton law of gravitation:
Since we know that
[tex]F = G*m1*m2/r^2[/tex]
Here
G - gravitational force
m -mass of the object
F1 = vertical force
[tex]F1 = (6.6726*10^-11*3*3)/0.52^2\\\\= 2.220*10^-9 N[/tex]
And, f2 = horizontal force
[tex]f2 = 6.6726*10^-11*3*3/0.36^2\\\\= 4.633*10^-9 N[/tex]
So here the force is
[tex]= \sqrt (2.220*10^-9)^2 + (4.633*10^-9)^2\\\\= 5.136*10^-9 N[/tex]
Hence, The magnitude of the resultant force (caused by the other two masses) on the mass at the origin should be [tex]5.136*10^9.[/tex]
Learn more about force here: https://brainly.com/question/14569246